Kajian analisis kos rawatan pesakit luar penyakit asma di Jabatan Pesakit Luar,Hospital Seremban - Safiah, B.,; Norhayati,; R.Faizan,; G.Marina,; K.Zaharah,; M.S.,; Prabakaran,; S.D.,; Haliza,; A.M. ,; Syed Mohammed,; A.J, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1998)
A cross-sectional study was conducted to analyse the management cost of asthma patients in the Outpatient Department of Hospital Seremban from the 20th October till 26th October, 1997. Forty asthmatic patients were specifically selected for this study. Data were obtained using guided questionaires and from the hospital’s financial statement. The study indicates that the overall cost of outpatient management for asthma was RM504.44 per patient for 1996. The hospital cost was RM395.11 per patient and the cost borne by patient was RM109.33. The hospital cost contributed 78.33% of the total cost as compared to the patient’s 21.67%. The total outpatient management cost of asthma in Malaysia for 1996 was estimated to be RM144,121,030.20. From this, the percentage of economic burden of illness for asthma in Malaysia for 1996 was calculated as 0.06% of the GNP.